Constituents and antiulcer effect of Alchornea glandulosa: Activation of cell proliferation in gastric mucosa during the healing process - Calvo, Tamara Regina; Lima, Zeila Pinheiro; Silva, Janaina Scaramelo; Rodrigues Ballesteros, Katia Veronica; Pellizzon, Claudia Helena; Hiruma-Lima, Clelia Akiko; Tamashiro, Jorge; Souza Brito, Alba Regina Monteiro; Takahira, Regina Kiomi [UNESP]; Vilegas, Wagner [UNESP] (Pharmaceutical Soc Japan, 2007)
Alchornea glandulosa (Euphorbiaceae) is a plant used in folk medicine as an antiulcer agent. Rats pretreated with methanolic extract obtained from the leaves of A. glandulosa (AG) showed a dose-dependent effect and significant reduction of gastric ulcers induced by absolute ethanol at the doses of 500 (57%) and 1000 mg/kg (35%) in relation to the control group. Pretreatment of mice with AG (500, 1000 mg/kg, p.o.) showed dose-dependent activity and significantly decreased the severity of lesions caused by HCl/ethanol and by non steroidal anti inflammatory drug-induced gastric lesions. Pretreatment with AG also induced antisecretory action via local and systemic routes and a significant decrease in the total gastric acid content. The gastroprotective effects of AG involved the participation of nitric oxide and increased levels of endogenous sulfhydryl compounds, which are defensive mechanisms of the gastrointestinal mucosa against aggressive factors. The ability of AG to heal gastric ulcers was evaluated after 14 consecutive days of treatment. The results showed that single oral administrations of AG (250 mg/kg/once daily) potently stimulates gastric epithelial cell proliferation that contributes to the accelerated healing of gastric ulcers induced by acetic acid. In addition, no subacute toxicity (body weight gain, vital organs, and serum biochemical parameters) was observed during treatment with AG. Phytochemical investigation of AG led to the isolation of myricetin-3-O-alpha-L-rhamnopyranoside, quercetin-3-O-alpha-L-arabinopyranoside, quercetin-3-O-beta-D-galactopyranoside, quercetin, amentoflavone, methyl gallate, gallic acid, and pterogynidine. We also established the phytochemical profile of AG with the quantification of total phenolic compounds. These compounds may contribute to the observed antiulcerogenic effects of AG.
Keywords: Alchornea glandulosa; proliferating cell nulear antigen (PCNA); antiulcer activity; phenolic compound